Energy Evolution Law and Fractal Characteristics of Different Rock Specimen Sizes on Dynamic Compression. (17th February 2022) - Zhou, Jun; Xu, Wensong; Zhao, Guangming; Meng, Xiangrui; Li, Yingming; Wu, Xukun; Li, Yuguang; Cheng, Xiang
Abstract : To explore the broken energy change and the specimen fragment influence of granite where the length-to-diameter ratio is 0.5–2, the SHPB device was used to perform dynamic loading on the granite specimens. The rock energy evolution law was analyzed by the energy time history curve, and according to rock fragment characteristics, the rock fractal dimension was calculated. The experimental results show that the rock energy-time history curve can be divided into four stages. The incident energy is independent of the length-to-diameter ratio of the rock specimens. When the length-to-diameter ratio of the rock specimens is 0.5–0.9, the difference of incident energy, transmitted energy, and reflection energy of rock specimens is small. With the length-to-diameter ratio increasing, the rock fragment size became larger. These rock fragments have good self-similarity. The rock specimen fractal dimension is at least 1.94, and the maximum D is 2.536. And with the length-to-diameter ratios increasing, the fractal dimension of rock specimens decreases. With the specimen fractal dimension increasing, the energy dissipation density of rock specimens also increases. The higher the energy dissipation density of a rock specimen, the more uniform rock fragments are.